SOCIAL CLASSES AND OCCUPATIONS OF JAVANESE SOCIETY IN 1950’s PORTRAYED IN “CIGARETTE GIRL” BY RATIH KUMALA - Robby Satria; Nafdi Irawan; Hermanda Octavian (IdeBahasa, 2026)
This study aims to identify the types of social classes and occupations represented in Javanese society in the 1950s as portrayed in Ratih Kumala’s Cigarette Girl. The study employs Max Weber’s theory of social class and Allan Swingewood’s sociology of literature. The data source is the novel Cigarette Girl, while the data consists of passages and dialogues related to social status and occupations. Data were collected through close reading and note-taking techniques and analysed using a qualitative descriptive method. The findings reveal three social classes: lower, middle, and upper classes. The lower class is represented by cigarette rollers, laborers, and servants, the middle class by teachers and educated workers, and the upper class by business owners and factory proprietors. These occupations reflect the social hierarchy of Javanese society in the 1950s. The study implies that literature can function as a social document that preserves historical representations of social class and occupational structures in society.